CdSe Nanoplatelets: Living Polymers. Issue 32 (22nd June 2016) - Jana, Santanu; Davidson, Patrick; Abécassis, Benjamin
Abstract: Colloidal CdSe nanoplatelets are considered to be excellent candidates for many applications in nanotechnology. One of the current challenges is to self‐assemble these colloidal quantum wells into large ordered structures to control their collective optical properties. We describe a simple and robust procedure to achieve controlled face‐to‐face self‐assembly of CdSe nanoplatelets into micron‐long polymer‐like threads made of up to ∼1000 particles. These structures are formed by addition of oleic acid to a stable colloidal dispersion of platelets, followed by slow drying and re‐dispersion. We could control the average length of the CdSe nanoplatelet threads by varying the amount of added oleic acid. These 1‐dimensional structures are flexible and feature a "living polymer" character because threads of a given length can be further grown through the addition of supplementary nanoplatelets at their reactive ends. Abstract : It's alive ! A method to controllably assemble CdSe nanoplatelets into micron‐long polymer‐like threads is reported. Threads of a given length could be further grown through addition of supplementary nanoparticles, giving these structures living polymer characteristics.